Evaluación multitemporal de la cobertura vegetal (2013 - 2022) de los páramos de la parroquia Isinliví, provincia de Cotopaxi. - Ugsha Toaquiza, Ángel Mauricio (2023)
The research was conducted in the moorlands of the parish of Isinliví, Sigchos canton, Cotopaxi province. The objective was to carry out a multitemporal evaluation of the change in vegetation cover of the moorlands over a nine-year period from 2013 to 2022. For which a comprehensive literature review of technical and geospatial criteria for the delimitation of the moors was conducted, the multitemporal analysis of the distribution and changes in vegetation cover was performed using Geographic Information Systems (GIS) through the processing of LandSat 8 satellite images, applying the CORINE Land Cover methodology adapted in Ecuador considering the protocol and guidelines established by the MAE, MAGAP and National Secretariat of Planning and Development for the classification of vegetation cover and land use of Continental Ecuador and mapping. The Isinliví moorlands are considered from 3200 masl and five cover classes were determined: herbaceous, shrub, agricultural, soil without vegetation cover and anthropic zone, during the study period had changes in vegetation cover 42.75% of the total delimited moor, the agricultural land had significant changes that has an increase of 363.19 ha amounting to a total of 1391.505 ha representing 26.66 % of the moor and the coverage that has the greatest loss is the shrub vegetation of 253.04 ha. It is concluded that during the study period there is an advance of the agricultural frontier towards the higher parts of the moor, being the cover that has the greatest expansion, replacing the natural vegetation, which influences the decrease in the capacity of ecosystem services provided by the moors to the population of the locality, mainly in the decrease of water supply for human consumption and irrigation